Análise dos eventos adversos em pacientes internados em um Hospital Universitário de Sergipe - Costa, Lucas Fontes (2018)
Adverse events (AE) were defined as unintentional injuries resulting from health care, not related to the natural course of the underlying disease, which cause measurable lesions in affected patients or prolongation of hospitalization or death. Hospitals are responsible for a significant and complex portion of the health care provided to patients, so the care provided to hospitalized patients is complex and requires that it be performed with quality and without unnecessary harm to the individual. The objective of this study was to evaluate the occurrence of adverse events in a University Hospital and to classify them as avoidable or non-avoidable. It is a study of secondary data. A simple random sample was selected from the records of patients hospitalized at the University Hospital of Aracaju-SE from 2014 to 2016. Several variables were investigated, the primary variable being the classification of the adverse event as avoidable and not preventable. We analyzed 121 cases of adverse events. Of these, 54 (44.6%) cases were judged to be avoidable, 63 (52.06%) as unavoidable, 4 (3.30%) could not be evaluated. Of the cases judged to be avoidable, 5 (9.25%) caused no harm to the patient, 28 (51.8%) caused mild damage, 13 (24.07%) moderate damage, 6 (11.1%) damages severe and 2 (3.70%) caused the patient to die. The rates of avoidable adverse events evidenced in this study are shown below the rates found in other Brazilian hospitals, mainly in comparison with studies done in hospitals in Rio de Janeiro. Nevertheless, these rates are still higher than those found in studies conducted in developed countries, which can serve as a basis for broader studies that can serve as tools for improving the quality of health care.